Acquisition and Discretionary Disclosure of Private Information and Its Implications for Firms' Productive Activities - Pae, Suil (Journal of Accounting Research, 1999)
Suil Pae, Acquisition and Discretionary Disclosure of Private Information and Its Implications for Firms' Productive Activities, Journal of Accounting Research, Vol. 37, No. 2 (Autumn, 1999), pp. 465-474